Species diversity of brackish water fishes and their associated endoparasites from the Tamala Fish Sanctuary of Kapatagan, Lanao del Norte, Philippines - ALLYSSA MARIE A. CALDERON; LADY JANE G. MORILLA; LEONARDO A. ESTAÑO (Society for Indonesian Biodiversity, 2024)
Abstract. Calderon AMA, Morilla LJG, Estaño LA. 2024. Species diversity of brackish water fishes and their associated endoparasites from the Tamala Fish Sanctuary of Kapatagan, Lanao del Norte, Philippines. Biodiversitas 25: 4745-4755. Fish plays a vital role in the aquatic ecosystem and is integral to human nutrition and food security. The survey of brackish water fishes and its associated endoparasites in Tamala Fish Sanctuary, Kapatagan, Lanao del Norte, Philippines, was carried out in August 2023 in three coastal barangays of Taguitic, Margos, and Lapinig. A total of 174 individuals belonging to 5 families were collected, comprising six species: Chanos chanos, Oreochromis niloticus, Oreochromis mossambicus, Glossogobius giuris, Mugil cephalus, and Ambassis nalua. Among the recorded species, M. cephalus harbors the highest abundance (35.63%) and can be found in all three sites, while O. mossambicus is the least abundant (2.87%) and is restricted to only one site. Endoparasites in these fish species, comprising nematode, trematode metacercariae, and Acanthogyrus sp., were also recovered in this study. The prevalence of infection is reported to be highest in Barangay Taguitic (42.86%), followed by Margos (25.45%) and Lapinig (10.48%). Among the species, C. chanos (35.71%) recorded the highest infection rate, followed by G. giuris (29.73%), O. niloticus (26.09%), and M. cephalus (1.61%). In contrast, two species, O. mossambicus and A. nalua, were not infected with endoparasites. Adult species (24.74%) also exhibit the highest prevalence rate compared to juveniles (9.09%). In terms of intensity, Lapinig (7.64±0.23) has the highest value in the site, followed by Margos (1.5±0.10), then Taguitic (1.4±0.17). With regards to species, G. giuris harbors the highest mean intensity (7.82±0.62), followed by C. chanos (1.6±0.17), O. niloticus (1.42±0.10), and M. cephalus (1±0.02). Furthermore, adult fish species (4.33±0.25) exhibit higher mean intensity than juveniles (1.41±0.04). The mean intensity per site, species, and age were significant (p<0.05). Endoparasites in these brackish water fish hosts are an excellent biological indicator in aquatic ecosystems. This study provides baseline data for further investigation on fish species diversity and its endoparasites in the area.